"Las Uniones de hecho y la liquidación de los bienes sociales y sus efectos jurídicos y económicos para las partes, de acuerdo a los juicios tramitados en los juzgados civiles y mercantiles del cantón Riobamba, en el periodo 2011-2012" - Sananay Auquilla, María Isabel (2016)
The theoretical foundation of this research work is mainly based on the theory of rationalism, because all theoretical, doctrinal and legal provisions will be analyzed critically, to reach the construction of a new knowledge about the problem, to investigate. As this is an eminently legal issue, legal and doctrinal studies will be conducted subject investigated, focusing primarily from the point of economically and socially. With regard to purely legal field, this research has the legal basis of the Constitution of the Republic of Ecuador, which is consistent with the researched topic and the socio-economic situation prevailing in the country, same as in Art. 68 determines that Union Made brings legal effect regarding extramarital relationships, durable and stable, with the same range of rights and obligations for families constituted through marriage, thus confirming the existence of the Law regulating Unions Done , built from Art. 222 to Art. 232 of the Civil Code Ecuadorian force. Therefore, it is undeniable that the legal issues arising from the full implementation of such provisions analogous to the system of community property, in many cases have generated and are generating series mistakes and injustices in the resolution of the problem, which warrants it is studied carefully and clearly. It is also important to note that, in order to find harmony and good judgment on the subject matter of the investigation, other than to refer to the above-cited legal provisions, it is necessary to structure topics, subtopics and concepts that have social, economic, family influence and work involving the acceptance of contracting this obligation by cohabitants must also point out the legal anti facts that produce partial or total nonentities that influence when issuing an opinion by civil and commercial authorities that administer justice in Riobamba city.